Poster 207: Effects of the COVID-19 Pandemic Lockdown on Access to Physical Therapy and Postoperative Sport Testing, Patient Reported Outcomes and Mental Health Scores Following Anterior Cruciate Ligament Reconstruction. Issue 7 (30th July 2022) - Martin, Maitland; Bradley, Helen; Hanley, Meghan; Griffin, Laurie; Godin, Jonathan; Dornan, Grant; Hackett, Thomas; Gruskay, Jordan
Objectives: When the COVID-19 pandemic caused mandatory closures of physical therapy offices and gyms in the winter and spring of 2020, many patients who had undergone ACL reconstruction (ACLR) over the previous months experienced unexpected interruptions in their rehabilitation process. The purpose of this study was to compare the sport testing, patient reported outcomes, and mental health scores between ACLR patients whose postoperative physical therapy may have been disrupted by the COVID-19 pandemic versus a control cohort of ACLR patients who completed their physical therapy the year prior to the pandemic. With the barriers created by COVID-19, we aimed to understand the relationship between access to physical therapy and objective/subjective patient outcomes as well as mental health scores. Methods: A retrospective study of prospectively collected data as well as prospective collection of patient questionnaires was performed. The control group was patients who underwent ACLR from November 2018 to March 2019 while the experimental "COVID" group consisted of patients who underwent ACLR from November 2019 through March 2020. Patients with concomitant meniscal injury were included, but any revision surgery or multiligamentous knee injury was excluded. Patients must have completed sport testing at 6-7 months postoperatively to be enrolled. Retrospective chart data including surgery specific data, patient specific demographic data, sport testing outcomes including thigh girth, quadriceps and hamstring index, Y-balance, Keiser leg press were reviewed. Patient reported outcome measures were collected through our institutional registry including IKDC, Lysholm, Tegner, SF-12 physical (PCS) and mental (MCS) component summaries, WOMAC and patient satisfaction. Finally, prospectively collected data included the ACL-RSI questionnaire as well as a study-specific questionnaire administered to the experimental population to assess the effect of the pandemic closures on their access to postoperative rehabilitation. Primary analysis compared sport testing outcomes at 6-7 months postoperative between the control group and the COVID group. Secondary analyses compared patient reported outcomes and patient satisfaction between groups. Subgroup analyses included comparisons within the COVID group based on ACL-RSI scores as well as access to PT and self-directed therapy during the pandemic. Results: A total of 50 patients with median age 34.5 years (52% female) were enrolled in the study, 25 in the control group and 25 in the COVID experimental group. Baseline demographics, surgery specific details and preoperative outcomes scores were similar between the groups, with the exception of a higher number of meniscal repairs performed in the COVID group (48% vs. 24%, p = 0.032). Median follow-up for sport testing was 7 months, and no statistically significant differences were seen between the two groups when comparing quadriceps index, hamstring index, Keiser power, Keiser reaction, y-balance, or girth testing (Table 1). Notably, more patients reached full flexion (≥140 degrees) in the control group than the COVID group (96% vs. 76%, p=0.05). Additionally, no differences were seen with regards to patient reported outcomes between the two groups.Subgroup analyses were then performed on the COVID group only. 48% of patients missed in-person physical therapy appointments due to the pandemic, while 68% of patients were able to perform self-directed physical therapy with the largest proportion reporting a frequency of 3-5x a week or higher. Interestingly, missing in-person physical therapy appointments was not statistically significantly associated with worsened postoperative sport testing, patient reported outcome or ACL-RSI scores. Meanwhile, those who participated in frequent (>3x per week) self-directed physical therapy reported improved ACL-RSI scores overall when compared to those patients only participating <2x per week, however only the risk appraisal subscore of the ACL-RSI was statistically significant (median 83 vs 38, p=0.03). Conclusions: Patients who underwent ACLR in the 4 months prior to the 2020 COVID-19 pandemic demonstrated a high rate of decreased access to physical therapy, but did not have significantly worsened sport testing, subjective outcome measures or mental health scores compared to a matched population undergoing ACLR in the same 4 months of 2019. Even when controlling for patients who specifically reported missing physical therapy appointments during the pandemic, no differences were seen. Participation in higher frequency of self-directed therapy led to improved ACL-RSI scores at 1- year postoperatively. These results may suggest that the bourgeoning availability of online and virtual therapy resources necessitated by the pandemic may have long-lasting value in supplementing postoperative rehabilitation, especially for those patients with limited access to in-person therapy due to time, distance, financial or insurance constraints. Additionally, these results have implications for any ongoing ACLR study that may have concerns about data validity in those patients whose perioperative period coincided with the COVID-19 pandemic. Table 1. Comparison of Experimental versus Control groups with respect to physical rehabilitation return to sport assessments.